Cover Image. (10th June 2020) - Gao, Wenqing; Yang, Jiaqian; Liu, Rong; Yan, Yinghua; Xie, Chengyi; Yu, Jiancheng; Tang, Keqi
Abstract : The cover image is based on the RESEARCH ARTICLE FGF‐21 biomarker detection at sub‐nanogram per mL level in human serum using normal‐flow liquid chromatography‐tandem mass spectrometry by Wenqing Gao et al., https://doi.org/10.1002/rcm.8817 .